ICASSP 2019 - 2019 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2019
DOI: 10.1109/icassp.2019.8682690
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Diagnosis of Alzheimer’s Disease Using Neural Network Language Models

Abstract: In today's aging society, the number of neurodegenerative diseases such as Alzheimer's disease (AD) increases. Reliable tools for automatic early screening as well as monitoring of AD patients are necessary. For that, semantic deficits have been shown to be useful indicators. We present a way to significantly improve the method introduced by Wankerl et al. [1]. The purely statistical approach of n-gram language models (LMs) is enhanced by using the rwthlm toolkit to create neural network language models (NNLMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 10 publications
1
54
2
Order By: Relevance
“…Recurrent Neural Networks (RNN), Long Short-Term Memory (LSTM), Convo-lutional Neural Network (CNN) and their combination model were applied to extract linguistic features from transcripts of a picture description task [13]. In [14], two n-gram neural network language models for healthy controls (HC) and patients with dementia were built respectively for detection. It has been proven that, for the same database, neural networks achieved a better result compared with traditional machine learning methods [11,14].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrent Neural Networks (RNN), Long Short-Term Memory (LSTM), Convo-lutional Neural Network (CNN) and their combination model were applied to extract linguistic features from transcripts of a picture description task [13]. In [14], two n-gram neural network language models for healthy controls (HC) and patients with dementia were built respectively for detection. It has been proven that, for the same database, neural networks achieved a better result compared with traditional machine learning methods [11,14].…”
Section: Related Workmentioning
confidence: 99%
“…In [14], two n-gram neural network language models for healthy controls (HC) and patients with dementia were built respectively for detection. It has been proven that, for the same database, neural networks achieved a better result compared with traditional machine learning methods [11,14]. The reason is, compared with deep learning methods, statistical models with handcrafted features are less robust and harder to design, as it requires more expert knowledge.…”
Section: Related Workmentioning
confidence: 99%
“…At the same time, this model achieved the best precision and F 1 scores with 6.55% and 2.80% improvements, respectively. Still, Fritsch et al [30] showed the best recall score with 1.66% difference although they did not report F 1 measure . The first advantage of our proposed methods compared to Fritsch et al [30] is that we train a single language model for both the AD and HC groups which helps the model to use samples from both classes for the desired task.…”
Section: Interpretation Of Resultsmentioning
confidence: 92%
“…Still, Fritsch et al [30] showed the best recall score with 1.66% difference although they did not report F 1 measure . The first advantage of our proposed methods compared to Fritsch et al [30] is that we train a single language model for both the AD and HC groups which helps the model to use samples from both classes for the desired task. The other advantage is that our models are highly pre-trained on large datasets which enables them to start training on new, smaller datasets with good initialization parameters and also avoid overfitting.…”
Section: Interpretation Of Resultsmentioning
confidence: 92%
“…Fritsch et al [30] used two different auto-regressive LSTM-based neural network language models to classify AD and HC transcripts of the Pitt corpus from the DementiaBank dataset. After that, Pan et al [31] worked on predicting AD using a stacked bidirectional LSTM and gated recurrent unit (GRU) layers equipped with a hierarchical attention mechanism.…”
Section: Deep Learning-based Approachesmentioning
confidence: 99%